Comparison of rituximab originator (MabThera®) to biosimilar (Truxima®) in patients with multiple sclerosis. (April 2021) - Perez, Thomas; Rico, Audrey; Boutière, Clémence; Maarouf, Adil; Roudot, Marjorie; Honoré, Stéphane; Pelletier, Jean; Bertault-Peres, Pierre; Audoin, Bertrand
Background: Rituximab's originator MabThera ® or Rituxan ® has demonstrated high efficacy in multiple sclerosis (MS). Because of the patent expiration, rituximab biosimilars have been developed. However, because a biosimilar is not the exact copy of the originator, the efficacy and safety of a biosimilar may significantly differ. Objectives: To compare the efficacy and safety of the biosimilar Truxima ® and the originator MabThera ® in MS. Methods: Consecutive MS patients receiving MabThera ® or Truxima ® were prospectively followed during 1 year after treatment introduction. Allocation to each treatment depended on the period of introduction and not the physician's choice. Lymphocyte count, clinical and magnetic resonance imaging (MRI) activity, Expanded Disability Status Scale (EDSS), and adverse events were compared. Results: In total, 105 and 40 patients received MabThera ® and Truxima ®, respectively. The two groups did not differ in baseline characteristics. Effect on CD19+ lymphocytes and disease activity were similar during follow-up. EDSS remained stable, with no difference between groups. Adverse events were similar between groups. Conclusion: The efficacy and safety of the rituximab biosimilar Truxima ® seem equivalent to the originator MabThera ® in MS patients. Truxima ® could represent a relatively cheap and safe therapeutic alternative to MabThera ® and could improve access to highly efficient therapy for MS in low- or middle-income countries.